Behavioral Disorders in Preschool Children in Groups of Preschool Educational Institutions: Causes and Ways to Overcome Them - Валентина Роменкова (Preschool Education: Global Trends)
The article presents the results of empirical studies of children with negative behavior in a kindergarten group, studying the causes of behavior disorders and testing the effectiveness of methods for overcoming these violations. Various approaches have been used to shape socially acceptable behavior in children.